UJI DAYA HAMBAT DAUN SENGGANI (Melastoma malabathricum L.) TERHADAP Trichophyton mentagrophytees DAN Candida albicans - Djaenudin Gholib (Research Center for Biology-Indonesian Institute of Sciences, 2009)
The in vitro study of